Pengaruh Pemahaman Peraturan Perpajakan, Kualitas Pelayanan Fiskus dan Kesadaran Wajib Pajak Terhadap Tingkat Kepatuhan WPOP - Astina, I Putu Surya; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of understanding tax laws, the quality of tax service, and the awareness of taxpayers on the level of taxpayer compliance of individuals. This research was conducted in the Tax Office Pratama Tabanan because the researcher saw that taxpayer personal compliance level in Tax Office Pratama Tabanan is relatively low. The population in this study are all individual taxpayers in the Tax Office Pratama Tabanan. The number of samples used in this study as many as 100 respondents from 102.607 population of the taxpayer personal that is still effective in the Tax Office Pratama Tabanan in 2015 calculated based on slovin formula with the method of determining the sample is accidental sampling method. Data collection was done by using questionnaire technique. Data analysis technique used is multiple linear regression analysis. Based on the results of the hypothesis in this reseach testing shows that the understanding of tax regulations, the quality of tax service and taxpayer awareness have a positive effect on taxpayer compliance level. This means that the higher level of understanding of tax regulations of a taxpayer, the better the quality of service provided by tax authorities to taxpayer and the higher the level of awareness of the taxpayer in fulfilling his obligation then will increase the compliance of the individual taxpayer in the Tax Office Pratama Tabanan.